(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a comprehensive analysis of the didactic foundations for enhancing the effectiveness of using digital educational resources in primary education. The study highlights the suitability of digital educational resources for the age and psychological characteristics of primary school students, their role in activating cognitive activity, and the possibilities for individualizing the learning process. The results of the study indicate that systematic and methodical use of digital educational resources improves the effectiveness of primary education.